NREM‐related parasomnias in Machado–Joseph disease: clinical and polysomnographic evaluation. (3rd September 2015) - Silva, Giselle Melo Fontes; Pedroso, José Luiz; Dos Santos, Diogo Fernandes; Braga‐Neto, Pedro; Do Prado, Lucila Bizari Fernandes; De Carvalho, Luciane Bizari Coin; Barsottini, Orlando G. P.; Do Prado, Gilmar Fernandes
Summary: Spinocerebellar ataxias (SCA) are autosomal dominant neurodegenerative disorders that affect the cerebellum and its connections, and have a marked clinical and genetic variability. Machado–Joseph disease (MJD) or spinocerebellar ataxia type 3 (SCA3)—MJD/SCA3—is the most common SCA worldwide. MJD/SCA3 is characterized classically by progressive ataxia and variable other motor and non‐motor symptoms. Sleep disorders are common, and include rapid eye movement (REM) sleep behaviour disorder (RBD), restless legs syndrome (RLS), insomnia, excessive daytime sleepiness, excessive fragmentary myoclonus and sleep apnea. This study aims to focus upon determining the presence or not of non‐REM (NREM)‐related parasomnias in MJD/SCA 3, using data from polysomnography (PSG) and clinical evaluation. Forty‐seven patients with clinical and genetic diagnosis of MJD/SCA3 and 47 control subjects were evaluated clinically and by polysomnography. MJD/SCA3 patients had a higher frequency of arousals from slow wave sleep ( P  < 0.001), parasomnia complaints (confusional arousal/sleep terrors, P  = 0.001; RBD, P  < 0.001; and nightmares, P  < 0.001), REM sleep without atonia ( P  < 0.001), periodic limb movements of sleep index (PLMSi) ( P  < 0.001), percentage of N3 sleep ( P  < 0.001) and percentage of N1 sleep ( P  < 0.001). These data show that NREM‐related parasomnias must be included in the spectrum of sleep disorders in MJD/SCA3 patients.